Усилители мощности Ku-диапазона для наземной станции спутниковой связи - Severgin, B. N.; Yakovlev, I. V.; Yatsyk, P. A.; Balaba, A. N. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
The results of the development of Ku-band power amplifiers (14.0–14.5 GHz) with output powers of 5 W and 25 W at 1 dB gain compression are presented. These amplifiers are part of the equipment set for a ground satellite communication station. A complete set of design documentation has been prepared for both amplifier types.